Under the Background of “New Normal”, Research on Constructing the Productive and Technical Preparation System Based on Lean Thinking for Locomotives -Take M Company as an Example - Ma Ming; Lu Tao (MATEC Web of Conferences, 2017)
This paper introduces the lean production theory and the application of lean production technology preparation system in related enterprises, put forward own views on a series of problems existing in the preparation of M company's production technology. Aiming at these problems, this paper combined with the practical application of lean thinking to the traditional production technology for system innovation and optimization, builds a clear M simulated production line concept, principles and framework, basically puts forward a complete set of methods and measures to construct the core technology of lean production system for part of the simulated production line.